2021
DOI: 10.17085/apm.20097
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of normal and low blood pressure regulation on the optic nerve sheath diameter in robot assisted laparoscopic radical prostatectomy

Abstract: Background: Robot-assisted laparoscopic radical prostatectomy is an advanced and popular surgical technique. However, increased intracranial pressure which is caused by CO2 pneumoperitoneum and Trendelenburg position is the main cerebrovascular effect. Measurement of optic nerve sheath diameter using ocular ultrasound is a noninvasive and reliable method for the assessment of intracranial pressure. The primary endpoint of this study was to identify whether low blood pressure regulation has any benefit in atten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Several previous studies have demonstrated excellent specificity and sensitivity between the ONSD and ICP, so intraoperative ICP changes can be evaluated by monitoring the ONSD ( 19 , 20 ). The cut-off value of the ONSD corresponding to intracranial hypertension (ICP > 20 mmHg) in previous studies was 5 mm ( 21 , 22 ). Our research showed that regardless of whether or not the IJV catheterization was performed, the ONSD reached more than 5 mm before returning to the supine position at the end of surgery.…”
Section: Discussionmentioning
confidence: 96%
“…Several previous studies have demonstrated excellent specificity and sensitivity between the ONSD and ICP, so intraoperative ICP changes can be evaluated by monitoring the ONSD ( 19 , 20 ). The cut-off value of the ONSD corresponding to intracranial hypertension (ICP > 20 mmHg) in previous studies was 5 mm ( 21 , 22 ). Our research showed that regardless of whether or not the IJV catheterization was performed, the ONSD reached more than 5 mm before returning to the supine position at the end of surgery.…”
Section: Discussionmentioning
confidence: 96%